Estimated attitude of students to cultural and leisure activities at the university - Azizakhon Abdullajonovna, Usmanova; Dildora Xashimovna, Kosimova; Barno Bakhtiyarovna, Abduraimova (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the analysis of students' evaluative attitude to the content of cultural and leisure activities (extracurricular activities) at the university. It presents data obtained as a result of a sociological survey among groups of students of different ages. Attention is focused on current issues related to extracurricular activities. The importance of the constant search for new forms and directions of extracurricular activities adequate to the modern value orientations of students is determined. Strengthening the interaction of deans, curators, subject teachers, and various student initiatives responsible for social monitoring of interests and the dynamics of solving youth problems, and their active involvement in the extracurricular sphere of activity in system management. The role of the psychological assistance service for students, the provision of regular advisory support to them, the organization of meaningful educational conversations and meetings with increased attention to the social behavior of young people, and the eradication of unwanted habits are noted. The necessity of forming independent knowledge and decision-making skills based on in-depth analysis and systematic replenishment of the baggage of practical skills is emphasized. Enrichment of the educational side of the educational process, its humanitarian and sociocultural orientation. Methods are proposed for a qualitative improvement in managerial activities at the university, namely: changing management of intra-organizational development, which requires a clear distribution of powers between levels of management; the formation of a program for motivation; the development of motivational technologies; the strengthening of outreach; and the creation of matrix structures for better interaction with the segments involved in social and cultural events at the university. In the field of ensuring social protection of students' interests, measures have been proposed to form a system of targeted support for subjects of extracurricular activities, especially among those who are less active, not involved, or suspended due to various personality-oriented reasons; assistance to the student trade union committee in maintaining social benefits and guarantees of students; and improving the system of legal and advisory support for students.